Simulation and optimization in an AGC system after deregulation. - Donde, V.
In this paper, the traditional automatic generation control (AGC) two-area system is modified to take into account the effect of bilateral contracts on the dynamics. The concept of distribution companies (DISCO) participation matrix to simulate these bilateral contracts is introduced and reflected in the two-area block diagram. Trajectory sensitivities are used to obtain optimal parameters of the system using a gradient Newton algorithm
Keywords: Automatic generation control optimisation; Automatic generation control simulation; Bilateral contracts; Distribution companies participation matrix; Electricity market deregulation; Gradient Newton algorithm; Trajectory sensitivities; Two-area block diagram; Two-area power system